Emergence of heat extremes attributable to anthropogenic influences. Issue 7 (2nd April 2016) - King, Andrew D.; Black, Mitchell T.; Min, Seung‐Ki; Fischer, Erich M.; Mitchell, Daniel M.; Harrington, Luke J.; Perkins‐Kirkpatrick, Sarah E.
Abstract: Climate scientists have demonstrated that a substantial fraction of the probability of numerous recent extreme events may be attributed to human‐induced climate change. However, it is likely that for temperature extremes occurring over previous decades a fraction of their probability was attributable to anthropogenic influences. We identify the first record‐breaking warm summers and years for which a discernible contribution can be attributed to human influence. We find a significant human contribution to the probability of record‐breaking global temperature events as early as the 1930s. Since then, all the last 16 record‐breaking hot years globally had an anthropogenic contribution to their probability of occurrence. Aerosol‐induced cooling delays the timing of a significant human contribution to record‐breaking events in some regions. Without human‐induced climate change recent hot summers and years would be very unlikely to have occurred. Key Points: We identify when the first attribution of heat extremes to anthropogenic climate change is possible Earliest attribution to anthropogenic influences in the 1930s globally and the 1980s in many regions Aerosol‐induced cooling delayed emergence of the anthropogenic signal in Northern Hemisphere regions